Augmented Expansion of Treg Cells From Healthy and Autoimmune Subjects via Adult Progenitor Cell Co-Culture - Reading, James L.; Roobrouck, Valerie D.; Hull, Caroline M.; Becker, Pablo Daniel; Beyens, Jelle; Valentin-Torres, Alice; Boardman, Dominic; Lamperti, Estefania Nova; Stubblefield, Samantha; Lombardi, Giovanna; Deans, Robert; Ting, Anthony E.; et al. (Frontiers in Immunology, 2021)
Recent clinical experience has demonstrated that adoptive regulatory T (Treg) cell therapy is a safe and feasible strategy to suppress immunopathology via induction of host tolerance to allo- and autoantigens. However, clinical trials continue to be compromised due to an inability to manufacture a sufficient Treg cell dose. Multipotent adult progenitor cells (MAPCⓇ) promote Treg cell differentiation in vitro, suggesting they may be repurposed to enhance ex vivo expansion of Tregs for adoptive cellular therapy. Here, we use a Good Manufacturing Practice (GMP) compatible Treg expansion platform to demonstrate that MAPC cell-co-cultured Tregs (MulTreg) exhibit a log-fold increase in yield across two independent cohorts, reducing time to target dose by an average of 30%. Enhanced expansion is coupled to a distinct Treg cell-intrinsic transcriptional program characterized by elevated expression of replication-related genes (CDK1, PLK1, CDC20), downregulation of progenitor and lymph node-homing molecules (LEF1 CCR7, SELL) and induction of intestinal and inflammatory tissue migratory markers (ITGA4, CXCR1) consistent with expression of a gut homing (CCR7lo β7hi) phenotype. Importantly, we find that MulTreg are more readily expanded from patients with autoimmune disease compared to matched Treg lines, suggesting clinical utility in gut and/or T helper type1 (Th1)-driven pathology associated with autoimmunity or transplantation. Relative to expanded Tregs, MulTreg retain equivalent and robust purity, FoxP3 Treg-Specific Demethylated Region (TSDR) demethylation, nominal effector cytokine production and potent suppression of Th1-driven antigen specific and polyclonal responses in vitro and xeno Graft vs Host Disease (xGvHD) in vivo. These data support the use of MAPC cell co-culture in adoptive Treg therapy platforms as a means to rescue expansion failure and reduce the time required to manufacture a stable, potently suppressive product.